Australian cancer nurses' experiences of burnout: Exploring the job demands and job resources of metropolitan cancer nurses during 2019–2020. Issue 1 (2nd January 2023) - Parkinson-Zarb, Lauren; Duff, Cameron; Wang, Ying; Mills, Jane
Abstract : Background: Existing studies that seek to understand nurses' experiences of burnout are dominated by cross-sectional, quantitative survey designs employing predetermined measures, often overlooking important job-related stressors that can be highly dependent on industry and professional contexts. Cancer nurses are a group of professionals who warrant special attention, as burnout in this profession is often attributed to high job demands and the challenge of caring for a vulnerable cohort of patients. A deeper understanding of the job demands associated with cancer nursing is required to provide insights about the work experiences of cancer nurses and identify aspects that mitigate burnout and stress. Purpose: This study describes the antecedents of burnout among Australian cancer nurses by focusing on the demands and resources inherent in their work. We aim to build on the existing literature by identifying job resources that may serve to mitigate the antecedents of burnout. Methodology/Approach: An in-depth interview study of cancer nurses across a spectrum of age and experience in Australian metropolitan public health care services was conducted over a 2-year period that coincided with the COVID-19 pandemic. The job demands and resources model framed this study of job-related factors associated with burnout and conversely job resources that may foster work engagement. Results: Patient aggression, workload, emotional demands, and abusive peers and managers were reported as distinct job demands, whereas job significance and supportive peers who demonstrated leadership, along with task variety, were identified as job resources. Conclusion: Australian cancer nurses work in an environment where job demands are increasingly disproportionate to job resources, leading to significant risk of burnout. Practice Implications: Our study identifies modifiable strategies for improving work conditions for this group who play a critical role in the health care system.